Kontribusi Dakwah Islam terhadap Nilai Nasionalisme di Kalangan Pemuda Muslim Kontribution of Islamic Da’wah to the Volue of Nasionalism Among Muslim Youth - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Yulia Nurhidayah; Annisa Yuliana; Suci Trimawarni (International Forum of Researchers and Lecturers, 2025)
This research explores the influential role of Islamic preaching, known as dakwah, in nurturing and reinforcing nationalistic values among young Muslims. It emphasizes the significance of integrating religious teachings with messages of patriotism to shape the mindset and attitudes of the youth towards their nation. Rather than viewing dakwah solely as a tool for religious propagation, this study positions it as a strategic and educational instrument that can instill a deep sense of national identity, unity, and active participation in national development.Employing a qualitative research methodology with a descriptive approach, this study analyzes various contemporary forms of dakwah, including religious lectures, Islamic study circles, digital platforms such as social media, and involvement in Islamic youth organizations. These channels are assessed for their effectiveness in conveying messages that resonate with the daily lives and societal roles of Muslim youth.The findings indicate that when Islamic values are harmoniously combined with national ideals, dakwah becomes a powerful vehicle for character building. It fosters a generation of young Muslims who are not only spiritually grounded but also exhibit strong civic awareness and a sense of responsibility towards preserving national unity and diversity. Ultimately, this research highlights the dual function of dakwah as both a spiritual guide and a catalyst for patriotic consciousness in the younger Muslim population.